2006
DOI: 10.1021/jf060513a
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Production and Processing of Conjugated Linoleic Acid-Rich Soy Oil

Abstract: Daily intake of conjugated linoleic acid (CLA), an anticarcinogenic, antiatherosclerotic, antimutagenic agent, and antioxidant, from dairy and meat products is substantially less than estimated required values. The objective of this study was to obtain CLA-rich soybean oil by a customized photochemical reaction system with an iodine catalyst and evaluate the effect of processing on iodine and iodo compounds after adsorption. After 144 h of irradiation, a total CLA yield of 24% (w/w) total oil was obtained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 12 publications
4
54
0
Order By: Relevance
“…As seen in Figure 8, the level of headspace oxygen decreased by CLA was faster than that of PCLA. Consistent with these results, CLA in the FFA form was extremely unstable (similar to DHA) 4 and had an oxidation rate considerably greater than LA and ACA. 4,5 Also, Yurawecz and others reported that CLA rapidly decomposed to form furan fatty acids when it was oxidized in air.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…As seen in Figure 8, the level of headspace oxygen decreased by CLA was faster than that of PCLA. Consistent with these results, CLA in the FFA form was extremely unstable (similar to DHA) 4 and had an oxidation rate considerably greater than LA and ACA. 4,5 Also, Yurawecz and others reported that CLA rapidly decomposed to form furan fatty acids when it was oxidized in air.…”
Section: Resultssupporting
confidence: 80%
“…Consistent with these results, CLA in the FFA form was extremely unstable (similar to DHA) 4 and had an oxidation rate considerably greater than LA and ACA. 4,5 Also, Yurawecz and others reported that CLA rapidly decomposed to form furan fatty acids when it was oxidized in air. 23 By contrast, PCLA had increased oxidative stability when compared with CLA.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Under irradiation, the I 2 possesses radical forming potential (GANGIDI & PROCTOR, 2004). By optimization of the process and performing the reaction in stirred batch photoreactor (JAIN & PROCTOR, 2006), a production of 240 mg CLA/g substrate was obtained.…”
Section: Obtaining Clas By Photochemical Methodsmentioning
confidence: 99%